THE MEDIATING EFFECT OF RETURN ON EQUITY ON THE RELATIONSHIP BETWEEN TAX AVOIDANCE AND STOCK PRICE - Hutabarat, Francis; Andrea Sihotang, Yolanda (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This study aims to determine whether it has the effect of Effective Tax Rate (ETR) on stock prices and Return On Equity (ROE) on stock prices. This study uses financial data obtained in annual reports and financial statements of 15 banks from 2014 - 2018. The research sample uses data from 15 Indonesian banks that have codes consisting of BBCA, AGRO, BBNI, BBKP, BBTN, BBRI, BDMN, BBYB, BJTM, BJBR, BNGA, BMRI, PNBM, MCOR, and INPC. Data analysis using t test, F statistical test, determination test and regression analysis. The results of this study indicate that Tax Avoidance has no effect on stock prices. However, with the mediating variable Return On Equity with significant result it shows that ROE fully mediates the relationship between tax avoidance and stock prices.